Development and initial clinical testing of a multiplexed circulating tumor cell assay in patients with clear cell renal cell carcinoma. Issue 9 (3rd March 2021) - Bade, Rory M.; Schehr, Jennifer L.; Emamekhoo, Hamid; Gibbs, Benjamin K.; Rodems, Tamara S.; Mannino, Matthew C.; Desotelle, Joshua A.; Heninger, Erika; Stahlfeld, Charlotte N.; Sperger, Jamie M.; Singh, Anupama; Wolfe, Serena K.; et al.
Abstract : Although therapeutic options for patients with advanced renal cell carcinoma (RCC) have increased in the past decade, no biomarkers are yet available for patient stratification or evaluation of therapy resistance. Given the dynamic and heterogeneous nature of clear cell RCC (ccRCC), tumor biopsies provide limited clinical utility, but liquid biopsies could overcome these limitations. Prior liquid biopsy approaches have lacked clinically relevant detection rates for patients with ccRCC. This study employed ccRCC‐specific markers, CAIX and CAXII, to identify circulating tumor cells (CTC) from patients with metastatic ccRCC. Distinct subtypes of ccRCC CTCs were evaluated for PD‐L1 and HLA‐I expression and correlated with patient response to therapy. CTC enumeration and expression of PD‐L1 and HLA‐I correlated with disease progression and treatment response, respectively. Longitudinal evaluation of a subset of patients demonstrated potential for CTC enumeration to serve as a pharmacodynamic biomarker. Further evaluation of phenotypic heterogeneity among CTCs is needed to better understand the clinical utility of this new biomarker. Abstract : Circulating tumor cells (CTCs) were evaluated for their expression of programmed death ligand‐1 (PD‐L1) and human leukocyte antigen class I (HLA‐I), so that biomarkers of therapeutic resistance of clear cell renal cell carcinoma can be developed. CTCs were captured with antibody‐conjugated magnetic beads against EpCAM and CAIX then probed for CAXII and CK expression using microfluidic technology.